2010
DOI: 10.2106/jbjs.h.01635
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Lesions and the Development of Osteoarthritis After Internal Fixation of Ankle Fractures

Abstract: Our findings show that initial cartilage damage seen arthroscopically following an ankle fracture is an independent predictor of the development of posttraumatic osteoarthritis. Specifically, lesions on the anterior and lateral aspects of the talus and on the medial malleolus correlate with an unfavorable clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
130
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(138 citation statements)
references
References 45 publications
3
130
0
5
Order By: Relevance
“…12 Taga et al 69 observed that 89% of patients with acute lateral ankle sprains presented with chondral lesions. It has been reported that cartilage damage anywhere in the ankle joint is an independent risk factor for ankle PTOA development, 70 supporting the notion that cartilage damage sustained at the time of ankle sprain may contribute to joint degeneration.…”
Section: Risk Factors For Ptoa Joint Injurymentioning
confidence: 65%
“…12 Taga et al 69 observed that 89% of patients with acute lateral ankle sprains presented with chondral lesions. It has been reported that cartilage damage anywhere in the ankle joint is an independent risk factor for ankle PTOA development, 70 supporting the notion that cartilage damage sustained at the time of ankle sprain may contribute to joint degeneration.…”
Section: Risk Factors For Ptoa Joint Injurymentioning
confidence: 65%
“…Whereas primary OA is the most common indication for total hip and total knee replacement, post-traumatic OA is the most common indication for ankle arthrodesis (Salzman et al 2005); 78% of patients with end-stage ankle OA are post-traumatic ). The severity of the initial fracture, articular cartilage damage, talocrural joint instability, and fracture malunion are the determinants of post-traumatic OA (Lindsjö 1981, DeSouza et al 1985, Wyss and Zollinger 1991, Soohoo et al 2009, Stufkens et al 2010.…”
Section: Post-traumatic Osteoarthritismentioning
confidence: 99%
“…Long-term studies (follow-up greater than ten years) evaluating risk factors for the development of ankle OA after malleolar fractures are sparse. Most of them are limited by small sample size [5][6][7][8][9] focusing on one or two factors. Only one study [8] assessed risk factors using statistical methods which allow for the presence of other risk factors.…”
Section: Introductionmentioning
confidence: 99%